Germanium coated vertically-aligned multiwall carbon nanotubes as lithium-ion battery anodes - Susantyoko, Rahmat Agung (2014)
The performance of polycrystalline and amorphous germanium (Ge) as anode active materials for lithium-ion batteries was studied systematically. Polycrystalline Ge on vertically-aligned multiwall carbon nanotube (MWCNT) arrays (MWCNT/c-Ge) and amorphous Ge on the arrays (MWCNT/a-Ge) were fabricated using a low pressure chemical vapor deposition system and a radio frequency sputtering system, respectively. The vertically-aligned MWCNT arrays were used as a platform to minimize pulverization problem. The MWCNT/a-Ge had a specific capacity of 1096.1 mAhg−1 at the rate of 162.4 mAg−1 at the 100th cycle. In comparison, the MWCNT/c-Ge only showed a specific capacity of 730.2 mAhg−1 at the rate of 162.4 mAg−1 at the 100th cycle. The MWCNT/a-Ge sample showed better performances as the MWCNT/a-Ge skipped the electrochemically-driven solid-state amorphization of crystalline Ge during the first lithiation.